Neutrophil Extracellular Traps Promote Aberrant Macrophages Activation in Behçet’s Disease - Li, Lu; Yu, Xin; Liu, Jinjing; Wang, Zhimian; Li, Chaoran; Shi, Jing; Sun, Luxi; Liu, Yi; Zhang, Fengchun; Chen, Hua; Zheng, Wenjie (Frontiers in Immunology, 2021)
Neutrophil extracellular traps (NETs) are upregulated and promote thrombosis in Behçet's disease (BD). However, whether NETs promote autoinflammation in BD remains unclear. This study aimed to investigate the potential role of NETs in promoting macrophage activation in BD. Firstly, we quantified NETs by measuring double-stranded DNA (dsDNA) using PicoGreen and calculating the proportion of NETosis. Then macrophages were stimulated with BD- or healthy controls (HC)-derived NETs, and IL-8 and TNF-α production and IFN-γ+ CD4+ T cells differentiation were measured using ELISA and flow cytometry, respectively. The protein components in NETs were analyzed by western blot. Macrophages were stimulated with Histone H4 neutralized NETs, and IL-8 and TNF-α production were measured using ELISA. The level of 8-hydroxydeoxyguanosine (8-OHdG) DNA in NETs was measured using ELISA. The levels of reactive oxygen species (ROS) in serum and neutrophils were measured using ROS probes by a microplate reader and flow cytometry. We found that circulating NETs and neutrophil-derived NETs were significantly higher in BD than HC. BD NETs stimulated macrophages produced higher levels of IL-8 and TNF-α, and promoted IFN-γ+ CD4+ T cells differentiation. BD NETs were enriched in Histone H4, and neutralizing Histone H4 abrogated the BD NETs-mediated IL-8 production by macrophages, but not TNF-α. Also, BD neutrophils produced more 8-OHdG DNA than HC neutrophils, and the percentage of 8-OHdG DNA in dsDNA from BD neutrophils was also higher than that of HC neutrophils. The ROS levels in serum and neutrophils were both higher in BD than HC. Our findings suggested that excessive BD NETs promoted macrophages activation and facilitated IFN-γ+ CD4+ T cells differentiation. Higher levels of Histone H4 and oxidized DNA in BD NETs might mediate macrophages hyperactivation.